The healthful plant‐based diet index as a tool for obesity prevention-The healthy lifestyle community program cohort 3 study - Christian Koeder; Dima Alzughayyar; Corinna Anand; Ragna‐Marie Kranz; Sarah Husain; Nora Schoch; Andreas Hahn; Heike Englert (Wiley, 2023)
Abstract Background World‐wide the prevalence of obesity is high, and promoting a shift toward more healthful and more plant‐based dietary patterns appears to be one promising strategy to address this issue. A dietary score to assess adherence to a healthy plant‐based diet is the healthful plant‐based diet index. While there is evidence from cohort studies that an increased healthful plant‐based diet index is associated with improved risk markers, evidence from intervention studies is still lacking. Methods A lifestyle intervention was conducted with mostly middle‐aged and elderly participants from the general population (n = 115). The intervention consisted of a 16‐month lifestyle program focusing on a healthy plant‐based diet, physical activity, stress management, and community support. Results After 10 weeks, significant improvements were seen in dietary quality, body weight, body mass index, waist circumference, total cholesterol, measured and calculated low‐density lipoprotein (LDL) cholesterol, oxidized LDL particles, non‐high‐density lipoprotein cholesterol, remnant cholesterol, glucose, insulin, blood pressure, and pulse pressure. After 16 months, significant decreases were seen in body weight (−1.8 kg), body mass index (−0.6 kg/m2), and measured LDL cholesterol (−12 mg/dl). Increases in the healthful plant‐based diet index were associated with risk marker improvements. Conclusions The recommendation of moving toward a plant‐based diet appears acceptable and actionable and may improve body weight. The healthful plant‐based diet index can be a useful parameter for intervention studies.